Chasing Arsinoe (Polis Chrysochous, Cyprus): A Sealed Early Hellenistic Cistern and Its Ceramic Assemblage - Olson, Brandon R.; Najbjerg, Tina; Moore, R. Scott (Journal of Hellenistic Pottery and Material Culture, 2018)
Between 1983 and 2009, Princeton University’s archaeological expedition to Polis Chrysochous uncovered large sections of the ancient city of Marion/Arsinoe, situated on the northwest coast of Cyprus (fig. 1). Marion, one of the smaller Iron Age kingdoms on Cyprus, was destroyed in 312 BCE by Ptolemy I Soter and its population was moved to Paphos. A generation later, Ptolemy’s son, Ptolemy II Philadelphos (285–246 BCE), founded a new city on the ruins of Marion, naming it Arsinoe after his wife and sister, probably shortly after her death in 270 BCE. Flourishing to this day, the town retained the name of the Ptolemaic queen throughout the Hellenistic, Roman, Late Antique, Byzantine, and Medieval periods, and it only seems to have faded from local memory during the three centuries of Ottoman occupation between 1571 and 1878.